Performance of the turbocharged engine Toyota Raize using Pertamax 92 and Pertamax Green 95 - Abbas, Aries; Sabiqunassabiqun, Sabiqunassabiqun; Saputra, Alfian Ady; Pahruzi, Rahmat; Kamal, Mustopa (JMPM (Jurnal Material dan Proses Manufaktur), 2024)
The automotive industry has experienced rapid technological advances in the development of more developed and efficient vehicles. An example is the Toyota Raize, which is equipped with a 3-cylinder turbocharged engine. Along with technological advances, issues have arisen regarding the use of optimal fuel to maintain engine performance. In the Indonesian market, Pertamina fuel is the main choice for consumers such as Pertamax 92 and Pertamax Green 95. The difference in octane values between the two raises questions about their impact on the performance of the Toyota Raize engine with a Turbocharger. A study was conducted on what fuel is better to use in a 3-cylinder turbocharged engine at varying engine speeds using experimental and theoretical research methods. The results showed that at engine speed 6000 RPM, the torque produced by Pertamax 92 reaches 130.8 Nm, while Pertamax Green 95 reaches 145.1 Nm. At the same speed, Engine power produced by Pertamax 92 reaches 110.2 HP, while Pertamax Green 95 records 122.2 HP. At low engine speed, Pertamax Green 95 is more efficient in fuel consumption whereas Pertamax 92 is more efficient at high speed. Pertamax Green 95 also produces a lower average CO2 concentration compared to Pertamax 92. In conclusion, Pertamax Green 95 fuel is more consistent and efficient and provides more optimal performance compared to Pertamax 92.